1993
DOI: 10.3171/jns.1993.78.5.0753
|View full text |Cite
|
Sign up to set email alerts
|

Significance of proliferating cell nuclear antigen index in predicting pituitary adenoma recurrence

Abstract: The recurrence rate of pituitary adenomas has been reported to be as high as 10% to 35% despite their generally benign nature. A monoclonal antibody directed against proliferating cell nuclear antigen (PCNA) was used to investigate whether the proliferative index might help to predict adenoma recurrence. This antigen is a nuclear protein identified as the auxiliary protein of deoxyribonucleic acid polymerase delta, and its gene expression correlates with cell proliferation. The authors studied 30 patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
64
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(68 citation statements)
references
References 31 publications
2
64
1
1
Order By: Relevance
“…However, there is some discrepancy in the literature with regard to the relapse rate and invasiveness of pituitary adenomas. Several authors have found a correlation between the Ki-67 LI and the relapse rate (9,22,(29)(30)(31)(32)(33)(34), while others have not (19,(35)(36)(37). However, most of these studies were heterogeneous, including different types of pituitary adenoma and various postoperative therapies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is some discrepancy in the literature with regard to the relapse rate and invasiveness of pituitary adenomas. Several authors have found a correlation between the Ki-67 LI and the relapse rate (9,22,(29)(30)(31)(32)(33)(34), while others have not (19,(35)(36)(37). However, most of these studies were heterogeneous, including different types of pituitary adenoma and various postoperative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…As is commonly seen in other endocrine neoplasms, Ki-67-positive cells were heterogeneously distributed throughout the tumor. Following studies on proliferative activity in pituitary adenomas (22)(23)(24), we evaluated the Ki-67 LI in the areas of the tumor where Ki-67-labelled nuclei were predominant. Thus, immunostained sections were screened under the microscope, and the areas containing the greatest number of Ki-67-stained nuclei were outlined with a pencil, allowing easy localization during image analysis.…”
Section: Pathological Studies and Mib-1 Immunostainingmentioning
confidence: 99%
“…These two markers are still being assessed. According to some authors (22), tumor size and PCNA immunoreactivity correlate. For others, Ki-67 is a more reliable marker, correlating well with proliferation potential and invasiveness (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…8,18) Various attempts have been made to establish markers that correlate with the clinical behavior of pituitary adenomas, such as invasion, recurrence, or malignancy. 1,2,5,[7][8][9][10][12][13][14][15]17,[19][20][21][22][23][24][27][28][29][30][31][32][33] Among the available methods of growth fraction determination, Ki-67 is a reliable marker for growth fraction determination of various specific cell cycle antigens. 1,12,32) Ki-67 is a protein which reacts with a …”
Section: Introductionmentioning
confidence: 99%